Front Cover: 3D Graphene Network Encapsulating Mesoporous ZnS Nanospheres as High‐Performance Anode Material in Sodium‐Ion Batteries (ChemElectroChem 12/2018). Issue 12 (30th May 2018) - Hu, Liang; Hu, Xiang; Lin, Zhoubin; Wen, Zhenhai
Abstract : The Front Cover shows the 3D interconnected network nanostructure with rGO enwrapping mesoporous ZnS nanospheres, which, owing to the highly conductive mesoporous structure, can potentially restrict large volume expansion upon sodiation and accordingly manifest a significantly improved cycling stability for the anode of sodium‐ion batteries. More information can be found in the Article by L. Hu et al. on page 1552 in Issue 12, 2018 (DOI: 10.1002/celc.201800412 ).